Shaking table tests on a masonry building monitored using smart bricks: Damage detection and localization. (11th April 2019) - Meoni, Andrea; D'Alessandro, Antonella; Cavalagli, Nicola; Gioffré, Massimiliano; Ubertini, Filippo
Summary: The seismic behavior of unreinforced masonry buildings is typically characterized by premature brittle collapse mechanisms that can cause serious consequences for the protection of human lives and for the preservation of historical and cultural heritage. Structural health monitoring can be a powerful tool enabling a quick post‐earthquake assessment of the structure's performance, but its applications are still scarce as a consequence of the severe limitations affecting off‐the‐shelf sensing technologies, in terms of local nature of the measurements, costs, as well as long‐term behavior, installation, and maintenance. To overcome some of these limitations, the authors have recently proposed a new sensing technology, called "smart brick, " that is a durable clay brick doped with stainless steel microfibers, working as a smart strain sensor for masonry buildings. This paper presents the first full‐scale application of smart bricks, used for detecting and localizing progressive earthquake‐induced damage in an unreinforced masonry building subjected to shaking table tests. Smart bricks are employed to detect changes in load paths on masonry walls, comparing strain measurements acquired after each step of the seismic sequence with those referring to the undamaged structure. Experimental results are interpreted using a 3D finite element model built to reproduce the shaking table tests. Overall, the results demonstrate that the smart bricks can effectively reveal local permanent changes in structural conditions following a progressive damage, therefore being apt for earthquake‐induced damage detection and localization.